Lamellibrachia sagami sp. nov., a new vestimentiferan tubeworm (Annelida: Siboglinidae) from Sagami Bay and several sites in the northwestern Pacific Ocean - Kobayashi, Genki; Miura, Tomoyuki; Kojima, Shigeaki (Zootaxa, 2015)
A new vestimentiferan tubeworm species of the genus Lamellibrachia Webb, 1969 is described. It was collected from cold seep areas off Hatsushima in Sagami Bay and at the Daini Tenryu Knoll in the Nankai Trough (606–1170 m depth). Lamellibrachia sagami sp. nov. differs from seven congeneric species in the following character states; showing a wider range of diameter of vestimental and trunk plaques than L. barhami, L. luymesi, L. satsuma and L. anaximandri; and having more numerous sheath lamellae (3–6 pairs) than L. juni (2–3 pairs) but fewer than L. victori (7 pairs) and L. columna (8–16 pairs).
World Polychaeta Database (WPolyDb). Article is open access